Techniques to improve intradialytic haemodynamic stability. Issue 6 (November 2018) - Gullapudi, V.R. Latha; Kazmi, Isma; Selby, Nicholas M.
Abstract : Purpose of review: Intra-dialytic hypotension (IDH) remains a significant problem for patients undergoing chronic haemodialysis. IDH causes symptoms that degrade patients' experience, compromises dialysis delivery and is strongly associated with adverse patient outcomes. Greater understanding of the link between IDH and dialysis-induced ischaemia in heart and brain has characterized mechanistic pathways, with repeated episodes of ischaemia resulting in organ dysfunction. This review provides updates from published evidence over the last 2 years across the range of potential interventions for IDH. Recent findings: A literature search was undertaken to identify articles published in peer review journals between January 2016 and April 2018 using terms 'intradialytic hypotension, ' 'haemodynamic instability, ' 'ESRF, ' 'renal replacement therapy, ' 'dialysis' in Medline and EMBASE and identified 58 references from which 15 articles were included in this review. Interventions included: cooling the dialysate; sodium profiling; convective therapies; strategies to minimize inter-dialytic weight gain (IDWG) and improve accuracy of target weight assessment; prescribing of antihypertensive medications; and carnitine supplementation. Summary: IDH remains a significant clinical problem. Recent evidence from the last 2 years does not support any major changes to current practice, with cooling of the dialysate and reduction of IDWG remaining cornerstones of management.